Association of a body shape index with cardiovascular risk profile in subjects with type 2 diabetes mellitus: an observational hospital-based study - Erum, Maheen; Chaudhury, Debasish; Ghotekar, L. H.; Islam, Seikh Yasir; Goswami, Anu (International Journal Of Community Medicine And Public Health, 2025)
Background: A body shape index (ABSI), has been shown to be a better predictor of all-cause mortality in incident hypertension, diabetes mellitus (DM) and cardiovascular diseases (CVDs). However, few studies explore association between ABSI and cardiovascular risk profile in patients with DM. Methods: This was an observational, hospital-based study conducted in the medical outpatient clinic of a tertiary-care center in Northern India. The study included diagnosed cases of type 2 DM (T2DM) (1:1 male-female ratio, aged ≥35 years). Anthropometric indices assessed included ABSI, WC, and body mass index (BMI). Primary outcome measures were HbA1c, systolic and diastolic blood pressure (SBP and DBP), and serum triglycerides (TG). The secondary outcome was urine albumin-to-creatinine ratio (UACR). Correlations between ABSI and cardiovascular risk factors were analyzed, and receiver operating characteristic (ROC) curve analysis was performed to compare the predictive ability of ABSI against WC and BMI. Results: No significant positive correlation was found (all p>0.05). Weak positive and negative correlations were observed between ABSI and HbA1c, TG and systolic blood pressure, UACR respectively. A significant negative correlation (p<0.05) was observed between ABSI and diastolic blood pressure (r=-0.243, p=0.023) in males. On assessment of area under curve (AUC) of ROC, ABSI, fared better than WC and BMI in association with HbA1c, TG, and blood pressure. Conclusions: Our study showed that there was no conclusive evidence to support ABSI as an accurate tool to gauge cardiovascular risks in patients with T2DM.